Exploring the impact of aging on motor imagery abilities: a systematic review with meta-analysis - Fierro-Marrero, José; González-Iglesias, Mario; Melis-Romeu, Alberto; López-Vidal, Javier Andrés; Paris-Alemany, Alba; La Touche, Roy (Frontiers in Public Health, 2025)
ObjectiveExplore motor imagery (MI) abilities in healthy older adults compared with healthy younger adults.MethodsA systematic review with meta-analysis.ResultsTwenty-seven cross-sectional studies were included. Meta-analyses explored MI abilities between healthy older and younger adults for the ability to generate kinesthetic (60–70 years: g = −0.24, 95%CI = −1.61, 1.13; 70–80 years: g = −1.29, 95%CI = −2.75, 0.17), and visual modality (g = −0.08, 95%CI = −0.71, 0.86); vividness in kinesthetic (g = 0.14, 95%CI = −0.13, 0.41), IV (g = 0.11, 95%CI = −0.16, 0.38), and EV modalities (g = 0.05, 95%CI = −0.15, 0.24); mental chronometry in timed-up and go (seconds = 0.63, 95%CI = −0.02, 1.27), and linear walk (seconds = 0.75, 95%CI = −0.55, 2.06); and MI-execution time congruence (performance overestimation) in linear walk (g = −0.02, 95%CI = −0.73, 0.69). Mental chronometry in upper limb movements was analyzed visually in forest plot indicating tendencies of greater time in older adults. Hand recognition in hand laterality judgment task visual analysis revealed a poorer accuracy, greater response time and lower efficiency in older adults.ConclusionVividness of MI in kinesthetic and visual modalities appears to be preserved in older adults. Tendencies for greater time in mental chronometry were observed in older adults in TUG, linear walk and upper limb tasks. Implicit MI assessed with hand laterality showed older adults have lower accuracy, longer response times and lower efficiency. The ability to generate MI in kinesthetic and visual modalities presented imprecise results, and no clear conclusions could be drawn on MI-execution temporal congruence due to imprecision. Further research is needed to potentially clarify these findings.Systematic review registrationPROSPERO: CRD42023384916.